Peta Tanah Digital : Sistem Inventaris Tanah Berbasis Web dengan Gis untuk Pengelolaan Modern di Kecamatan Parakan Kabupaten Temanggung Jawa Tengah - Agung Yuliyanto Nugroho; Annisa Fikria Shimbun (Jurnal Informasi, Sains dan Teknologi, 2023)
Land ownership disputes are one of the legal and social problems that often occur in various countries, including in Indonesia. These disputes generally arise due to ambiguity or inaccuracies in the administration of land ownership. One of the main causes of this dispute is the absence of a letter or proof of legal land ownership, in addition to this can occur in the distribution of inheritance caused by internal factors, such as parental grants to prospective heirs, but it is unfair and not accompanied by a grant deed, married couples (as prospective heirs) who do not have children or descendants, the greed of the heirs, the incomprehension of the heirs, the mistake in upholding the siri' and the delay in the distribution of inheritance. The WEBGIS-Based Land Inventory System makes it easier for village or district government officials to record land ownership so that the increase in fulfillment of leter C is reduced, the process of searching and changing data does not take long and the public can find out land information along with the history of ownership transfer shown on the online map.